Diagnosis of level I: “ACERCAR” and II: Promotion of sustainable production and consumption of Business Environmental Management Program in Bogotá D.C. (2017)
(Eng) Evaluation and feedback are essential in all management processes, especially when actions are aimed at target level of a local authority, especially as complex as a capital district. This document presents the main findings of the diagnosis that was made in Levels I and II of the Environmental Business Management Program (GAE by its acronym in spanish) in Bogota. For its development, management reports generated by the Secretaría Distrital de Ambiente (SDA) were consulted, and the approach of the actions in levels I and II quantitatively and qualitatively were evaluated. On the other hand, surveys were formulated and applied to both participating and external companies, the first ones, in spaces of the GAE Program, provided by the SDA, and the second through visits, phone calls and electronic mails. The analysis and processing of these data allowed us to establish the impact of levels I and II of the GAE Program on the perception, support and management of Cleaner Production (CP) and Sustainable Consumption (SC) in companies grounded in Bogota, the Capital District. Finally, based on the above, as well as in consultations with external entities, the recommendations for the planning and execution in order to contribute to the continuous improvement in the promotion of CP and SC in the productive sector were made.